Part II – imidazolines and rhinitis medicamentosa: how can we tackle the rebound dilemma? - Stinson, Rebecca J.; Sadofsky, Laura R. (Frontiers in Pharmacology, 2025)
Rhinitis medicamentosa is the state of chronic congestion experienced from the prolonged or excessive use of nasal vasoconstrictors, typically used in the treatment of nasal congestion. Although a minor ailment, nasal congestion is a bothersome symptom for many allergic and non-allergic rhinitis sufferers. To alleviate symptoms, patients turn to over-the-counter topical nasal decongestants, with imidazolines often being the active ingredient of choice, as they provide rapid and long-lasting symptom relief, via vasoconstriction within the nasal mucosa. When used correctly, nasal vasoconstrictors are considered safe. However, misuse and deviation away from the recommended frequency of dose or maximum length of treatment can result initially in acute rebound congestion and if continued, rhinitis medicamentosa (RM). The pathophysiology and mechanisms of RM have not been fully elucidated and are complicated by difficulties in determining where the underlying disease ends, and RM begins. RM is characterised by the presence of chronic nasal congestion which responds less effectively and for progressively shorter periods to nasal vasoconstrictor treatments. Consequently, patients try to relieve symptoms by taking the nasal vasoconstrictor more frequently or at higher doses, which ultimately exacerbates the congestion further and creates a dependency on the nasal vasoconstrictor. Why RM develops is unclear, hypothesised mechanisms include structural, functional and inflammatory changes in the nasal mucosa, changes in receptor sensitivity or innervation pathways. To which extent this is solely in response to the use of imidazoline derivates or related to the presence of preservatives in topical nasal treatments is yet to be determined. Although treatment options exist for RM, prevention may be the best medicine. Provision of better education around the use of nasal vasoconstrictions, coupled with preservative free formulations and lowest possible dose delivery, may help to reduce the likelihood of developing the disease from the outset, reducing the burden on both the patient and healthcare providers.